Prognostic role of ABO blood group in patients with unresectable hepatocellular carcinoma after transarterial chemoembolization - Li Q; Wu T; Ma X; Jing L; Han L; Guo H (Dove Medical Press, 2018)
Qing Li,1,* Tao Wu,1,* Xiao-An Ma,2,* Li Jing,1 Li-Li Han,3 Hui Guo1 1Department of Medical Oncology, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China; 2Department of General Surgery, Xi’an Central Hospital, Xi’an, Shaanxi, People’s Republic of China; 3Department of Oncology, The Second Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China *These authors contributed equally to this work Background: The association of ABO blood group with prognosis of several malignancies has been established. However, its role in hepatocellular carcinoma (HCC) remains unclear.Patients and methods: In this study, we investigated the prognostic role of ABO blood group in unresectable HCC patients receiving transarterial chemoembolization (TACE) as an initial treatment. Medical records of 2,611 HCC patients were collected, and clinical data of 282 unresectable HCC patients receiving TACE were ultimately analyzed retrospectively. A prognostic nomogram was generated for predicting 1-, 2-, and 3-year overall survival (OS) probability. A total of 114 (40.4%), 69 (24.5%), 64 (22.7%), and 35 (12.4%) HCC patients had blood groups O, A, B, and AB, respectively.Results: The median OS times for patients with blood groups O, A, B, and AB were 24, 23, 20, and 20 months, respectively. Patients with blood group AB (hazard ratio [HR]=2.050, 95% confidence interval [CI], 1.331–3.157, P=0.001) or group non-O (HR=1.479, 95% CI, 1.110–1.972, P=0.008) had a poorer OS than those with blood group O. The prognostic nomogram, with a c-index of 0.701, was modest in predicting OS of unresectable HCC patients.Conclusion: Patients with non-O blood group, particularly blood group AB, had a worse OS compared with those having blood type O. ABO blood group can predict the prognosis in patients with unresectable HCC undergoing TACE as an initial therapy. Further external validation in larger cohorts is necessary to confirm their usefulness in clinical practice. Keywords: prognosis, ABO blood group, overall survival, liver cancer, transarterial chemoembolization